Retrospective Identification of Early Autochthonous Case of Crimean-Congo Hemorrhagic Fever, Spain, 2013 - Ana Negredo; María Sánchez-Ledesma; Francisco Llorente; Mayte Pérez-Olmeda; Moncef Belhassen-García; David González-Calle; María Paz Sánchez-Seco; Miguel Ángel Jiménez-Clavero (Emerging Infectious Diseases, 2021)
Before this report, 7 autochthonous human cases of Crimean-Congo hemorrhagic fever had been reported in Spain, all occurring since 2016. We describe the retrospective identification of an eighth case dating back to 2013. This study highlights that the earliest cases of an emerging disease are often difficult to recognize.